Triple bag hermetic technology for controlling a bruchid (Spermophagus sp.) (Coleoptera, Chrysomelidae) in stored Hibiscus sabdariffa grain. (October 2016) - Amadou, L.; Baoua, I.B.; Baributsa, D.; Williams, S.B.; Murdock, L.L.
Abstract: We assessed the performance of hermetic triple layer Purdue Improved Crop Storage (PICS) bags for protecting Hibiscus sabdariffa grain against storage insects. The major storage pest in the grain was a bruchid, Spermophagus sp.. When we stored infested H. sabdariffa grain for six months in the woven polypropylene bags typically used by farmers, the Spermophagus population increased 33-fold over that initially present. The mean number of emergence holes per 100 seeds increased from 3.3 holes to 35.4 holes during this time period, while grain held for the same length of time in PICS bags experienced no increase in the numbers of holes. Grain weight loss in the woven control bags was 8.6% while no weight loss was observed in the PICS bags. Seed germination rates of grain held in woven bags for six months dropped significantly while germination of grain held in PICS bags did not change from the initial value. PICS bags can be used to safely store Hibiscus grain after harvest to protect against a major insect pest. Highlights: Hibiscus sabdariffa is produced by low resource farmers in Sub-Saharan Africa. Stored Hibiscus grain is attacked by a bruchid of the genus Spermophagus . Spermophagus infestations severely damage the grain and reduce germination. Storage in triple layer hermetic PICS bags prevents losses due to Spermophagus .